2019
DOI: 10.1530/joe-19-0022
|View full text |Cite
|
Sign up to set email alerts
|

Circadian production of melatonin in cartilage modifies rhythmic gene expression

Abstract: Endochondral ossification, including bone growth and other metabolic events, is regulated by circadian rhythms. Herein, we provide evidence that melatonin has a direct effect on the circadian rhythm of chondrocytes. We detected mRNA expression of the genes which encode the melatonin-synthesizing enzymes AANAT (arylalkylamine N-acetyltransferase) and HIOMT (hydroxyindole O-methyltransferase), as well as the melatonin receptors MT1 and MT2 in mouse primary chondrocytes and cartilage. Production of melatonin was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 30 publications
2
15
2
Order By: Relevance
“…The dose-response relationship between PTHrP expression level and melatonin concentration registered at least during the treatment period (MEL1 and MEL2) contradicts the negative correlation of those two parameters stipulated by Abbink et al [49]. Indeed, another study on primary BALB/c mouse chondrocytes [50] supports our finding about melatonin's capacity to upregulate PTHrP expression. Additionally, an association between abnormally developing bones and a high expression of PTHrP on Sparus aurata was already described [51].…”
Section: Discussioncontrasting
confidence: 65%
“…The dose-response relationship between PTHrP expression level and melatonin concentration registered at least during the treatment period (MEL1 and MEL2) contradicts the negative correlation of those two parameters stipulated by Abbink et al [49]. Indeed, another study on primary BALB/c mouse chondrocytes [50] supports our finding about melatonin's capacity to upregulate PTHrP expression. Additionally, an association between abnormally developing bones and a high expression of PTHrP on Sparus aurata was already described [51].…”
Section: Discussioncontrasting
confidence: 65%
“…Mechanical unloading (reduced mechanical stress on the bone) induces significant bone loss, as evidenced by disuse osteoporosis, which is a critical issue for bedridden patients and astronauts [1,2]. Mechanical loading is a crucial factor controlling bone mass [2].…”
Section: Introductionmentioning
confidence: 99%
“…And several studies have demonstrated the regulation of integrin acting on retina 157,158 . The addition of melatonin results in increased growth of chondrocytes and promotes expression of typical cartilage components, such as COL2A1, aggrecan, and SOX9 159 …”
Section: Evidence That Circadian Clock Coordinates the Developmental mentioning
confidence: 99%